2022
DOI: 10.1088/1873-7005/ac522c
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation of ventilation bubble dynamics around a vertically moving cylinder under reduced ambient pressure

Abstract: Ventilation bubble is widely used to reduce friction drag of object travelling in fluid. A large number of experimental studies are performed on the ventilation bubble in water tunnel, while little is known about it around vertically moving cylinder under reduced pressure. We aim to investigate dynamics of the ventilation bubble in vertically moving case. To support the study, a specialized experiment set-up is designed, based on which images of ventilation bubble around vertically moving cylinder under reduce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Their results showed that this model could more accurately predict the loads on the object than linear models. Furthermore, many researchers [18][19][20][21][22][23] have set up experimental platforms to investigate the phenomenon of cavitation during the process of water exit, the morphology of the ventilated cavity, the deformation of the free surface, the movement of the vehicle, and the characteristics of load and have reported satisfactory results. A considerable amount of research [24][25][26][27][28][29][30] has also been devoted to the ventilated cavity of underwater vehicles.…”
Section: Introductionmentioning
confidence: 99%
“…Their results showed that this model could more accurately predict the loads on the object than linear models. Furthermore, many researchers [18][19][20][21][22][23] have set up experimental platforms to investigate the phenomenon of cavitation during the process of water exit, the morphology of the ventilated cavity, the deformation of the free surface, the movement of the vehicle, and the characteristics of load and have reported satisfactory results. A considerable amount of research [24][25][26][27][28][29][30] has also been devoted to the ventilated cavity of underwater vehicles.…”
Section: Introductionmentioning
confidence: 99%